Case Report Of Transverse Myelitis: Rare Neurological Complications Of Herpes Zoster Virus - Mukhammad Arif Hadi Khoiruddin; Ika Sedar Wasis Sasono (Journal of Agromedicine and Medical Sciences, 2023)
Introduction: Transverse myelitis is a rare disease that accured by incident 0,3%-1% Though it rare happened transverse myelitis deserve to diccus because the variant presentation that make clinical challenge to dianosis to pre-observation for upgrade’s prognosis. Case Report: we reported case of transverse myelitis that was neurology complication to rare herpes zoster virus. Woman 27 years old came by early complaint of tingling fever, pain, shiver continue on foot and the right hand. After got well, patient cameback to her disease bacause of the worst condition that cold not mover her left foot. Diagnosis transverse myelitis could stand through clinical sympton and magnetic resonance imaging (MRI) patient that came by her skin of hipopigment have to always considere the happening of transverse myelitis and lost control of defecate on neurologi observation being got paraplegi, monoparese extremitas superior, and hipoanesthesia dermatom C5 on low grade. We got observation of MRI to the level cervicothoracal that show long segment hipeintensity introdural intra medullary to the level craniovertebral junction so C5 and T2 so on that involved 2/3 spinal cord that strength described transverse myelitis. Discussion: Varicella zoster virus cou caused neurologis complication, the of transverse myelitis, of it is sign and sympton like pain, sencoric trouble, weakness on arm and foot, and the problem bladder and intestines. This symptom often occured unilaterally , Ipsilateral toward rash then become bilaterally. Intervention should the customize with pattient complaint: The implement combination asiklovir and high close steroid’s inject significantly relieve the pattient complaining but still occured paraplegi. Keywords: Transverse myelitis, HZV, neurological complication